Safety and efficacy of coated flow diverters in the treatment of cerebral aneurysms during single antiplatelet therapy: a multicenter study - Görtz, Lukas; Hohenstatt, Sophia; Vollherbst, Dominik; Weyland, Charlotte S.; Nikoubashman, Omid; Gronemann, Christian; Pflaeging, Muriel; Siebert, Eberhard; Bohner, Georg; Zopfs, David; Schlamann, Marc; Liebig, Thomas; et al. (Interventional neuroradiology, 2024)
Objective - This multicenter study evaluates the safety and efficacy of coated flow diverters (cFDs) for the treatment of cerebral aneurysms under single antiplatelet therapy (SAPT). - Methods - This is a retrospective, observational study of 41 patients (median age: 58 years) with 41 aneurysms (median size: 7 mm, 29 [71%] saccular, 9 [22%] ruptured) treated with cFDs at four neurovascular centers between 2020 and 2023. Scheduled cases received continuous SAPT starting seven days before the procedure. Emergency cases were treated with tirofiban followed by SAPT loading. The safety endpoint was ischemic complications occurring during the procedure and within four months of clinical follow-up. - Results - The Pipeline Vantage or Flex Shield was used in 26 (63%) procedures, the FRED X in 12 (29%), the p48/64 Hydrophilic Polymer Coating in 2 (5%), and the Derivo Embolization Device 2heal in 1 (2%). Single antiplatelet therapy consisted of prasugrel in 27 (66%) patients, ticagrelor in 9 (22%), and ASA in 5 (12%). There were 2 (5%) early ischemic complications (one minor stroke and one transient ischemic attack). There were no late ischemic complications in the four-month follow-up of 35 patients. The six dropouts included four nontreatment-related deaths after subarachnoid hemorrhage and two patients with a poor outcome after subarachnoid hemorrhage. Complete and favorable occlusion rates (median: 7 months) were 75% (27/36) and 89% (32/36), respectively. - Conclusions - Coated flow diverter implantation in the setting of SAPT was safe and effective and warrants confirmation in a prospective comparative trial.